Computational Exploration of the Structural, Electronic and Nonlinear Optical Properties of Substituted Piperidine Scaffold: A DFT and Molecular Docking Approach - Baskar, G.; Veeramalini, J.B.; Jebaraj, J. Winfred (Asian Journal of Chemistry, 2026)
An investigation into the structural, electronic and reactive properties of a substituted piperidine scaffold were conducted using density functional theory (DFT) at the B3LYP/6-31 G(d) level of theory. Molecular geometry optimization established a stable equilibrium structure. Frontier molecular orbital (FMO) analysis suggested a HOMO-LUMO energy gap of 5.6665 eV, consistent with high kinetic stability. Molecular electrostatic potential (MEP) mapping and Mulliken charge analysis identified the oxygen atoms as the principal nucleophilic centers, while the hydroxyl hydrogen bears a pronounced electrophilic character. Natural bond orbital (NBO) and non-covalent interaction (NCI) analyses quantified pronounced hyperconjugative stabilization and a complex network of hydrogen bonding interactions, particularly across the hydrazone linkage, which exhibited a Mayer bond order of 1.6852. The first-order hyper-polarizability was calculated as 1.044 × 10–30 esu, approximately 2.8-fold higher than that of urea, supporting the potential of the molecule for nonlinear optical (NLO) applications. Thermodynamic parameters exhibited strong temperature dependence, while STM and ALIE surface analyses identified the nitrogen-rich core as an electronically active region. Molecular docking against the 1BP1 protein yielded a binding energy of -6.4 kcal/mol, with hydrogen-bonding interactions involving VAL A:433 and PRO A:430. These computational findings support the relevance of the molecular scaffold for further investigation in medicinal chemistry and optoelectronic applications.